Naturalistic philosophy in Edith Wharton’s “The House of Mirth” - Білинська, Х. В. (Studia Philologica, 2019)
The article is dedicated to the issue of naturalistic philosophy in Edith Wharton’s “The House of Mirth”. The influence of heredity and environment on the protagonists’ development and behaviour has been stated. Edith Wharton emphasizes the heredity of two characters — Lily Bart and Lawrence Selden. She portrays how the qualities inherited from the parents and further intensified by upbringing affect their future welfare. The protagonists are under total control of their environment — the New York leisure-class society. It determines their motives and actions, as well as has overwhelming effect on their personal lives, ensured by means of gossip and public censure. Edith Wharton has been proved to use repetition of the same actions and habits in order to achieve the effect of stuckness in one place. Incessant social events of the American elite, held in accordance with a strict protocol, lead to thingification of people. The society itself turns into a fetish. As a result, the typical naturalistic notions of “life as suffering” and “life as a prison” are achieved. After a thorough investigation, it has been summarized that Edith Wharton’s “The House of Mirth” should be considered as a representative of the optimistic and idealistic stream of American naturalism.